Practical Synthesis of 7-Azaserotonin and 7-Azamelatonin - Fukuya, Ren; Yamada, Koji; Nishi, Takahide (Synlett, 2022)
A practical method for synthesizing 7-azaserotonin and 7-azamelatonin was developed by using 3-bromo-5-methoxy-1-tosyl-2,3-dihydro-1H-pyrrolo[2,3-b]pyridin-2-ol as a starting material. This compound is a useful reactant for the formal C3-electrophilic reaction. The lactone derivative obtained by the reaction with Meldrum’s acid was used as a key intermediate, in which the C2 unit was introduced into the 7-azaindole skeleton.
Keywords: azaserotonin; azamelatonin; medicinal chemistry